TRANSFORMATION OF THE PRINCIPLES OF HUMANISM AND RESPONSIBILITY IN THE CONTEXT OF MODERN ENVIRONMENTAL ETHICS AND THE CONCEPT OF SUSTAINABLE DEVELOPMENT - Shorina, Tetiana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. Today the rate of environmental damage is increasing across planet and this calls into question the safety and very existence of human society, as well as its ability to adequately respond to emerging threats and challenges. The direction of the solution of modern antagonism in human existence has long been outlined in philosophy, social science and ethics, and finds its concrete embodiment in the development of environmental ethics. The central concepts of this philosophical discipline - the concept of environmental and social responsibility - become key value orientations. Research methods. The theory and method of discourse analysis, the method of comparative analysis, as well as system-logical, dialectic, analytical, synthetic and structural research methods are applied. The aim and tasks. The aim is to study the transformation of the values of humanism and responsibility in the context of the assertion of the principles of environmental ethics. At the same time, significant philosophical and scientific concepts of ecological orientation are considered, which form the methodological and categorical basis of modern environmental ethics and social ideas aboutharmonious social organization. The tasks are: to clarify the contradictions between the worldview attitudes of biocentrism and anthropocentrism, as well as to specify examples of social responsibility within the framework of the ecological trend. Research results. In the history of scientific and philosophical thought, there are a number of concepts whose contribution to the formation of ecological consciousness and practice is undeniably significant.The article briefly discusses the noospheric ideas of V. Vernadsky, the principle of "reverence for life" by A. Schweitzer, the principle of responsibility of ethics by H. Jonas, the ideas of co-evolution of nature and society by M. Moiseev, worldview principles of the concept of sustainable development. These concepts and those involved in them show a general tendency of the social consciousness to understand the degree of one’s own responsibility for historical progress and self-improvement of one’s forces. The principle of humanism is comprehended in a new way: now it extends not only to the area of interaction between people, but gradually also to the attitude to nature, to the Other. The dominants of ecological ethics are shifting from anthropocentrism towards biocentrism. The paper clarifies the concepts of social responsibility and corporate social responsibility, including concrete examples of greening and socialization of economic activity, in particular, some companies in the fashion industry.Discussion.The logical and moral ambiguity of affirming the values of biocentrism instead of anthropocentrism is indicated. The new humanism reconsiders the place of man in the Cosmos, depriving him of his privileged status and thus devalues or transforms the content of the right to subjectivity. Recognition of the equality of the Other (first of all, the animal ones) with oneself, firstly, attracts animals into the legal field of relations, endowing them with their own rights. But it is obvious that the whole struggle for the rights of animals and the corresponding discussions take place without the participation and initiative of the party whose rights were violated, which cannot be considered a manifestation of subjectivity and, accordingly, does not give grounds for the equality of a person with another living being. Conclusion. The ideas of modern humanism are embodied in the concept of sustainable development and coincide with the principles of environmental ethics. The latter appeals not to the anthropological nature of man, not to the absolute unconditional goodness in the world, but is due to the solution of a specific problem situation -the global social and environmental crisis and optimism in the ability of mankind to overcome it. Today, the “spirit” of change permeates both theoretical social consciousness (a set of philosophical and scientific concepts of society harmonization) and public opinion (moods and feelings of justice, compassion, mercy, responsibility towards people and nature). One of the tools for implementing the ideas of sustainable development is the development of corporate social responsibility practices, primarily in the business sector.